A Theological Interrogation of Artificial Intelligence (AI) in the Face of God's Creative Power - Owoade, Samuel Oluwatosin; Olubitan, Adesina Abiodun (NIU Journal of Humanities, 2026)
Artificial Intelligence is playing an increasingly transformative role in knowledge creation, learning spaces and international innovation, and challenges the nature and limits of human creativity in profound theological and philosophical ways. In this paper, I am asking for an interdisciplinary analysis of this question: Is Artificial Intelligence a successful competition with God's creative powers, or is it simply the extension of human ingenuity within the parameters set by God? The study utilises classical theological teachings and concepts, including creatio ex nihilo, Imago Dei and divine sovereignty, to analyse the ontological, divine and ethical aspects of artificial creativity. This paper situates itself within the broader context of innovation and sustainability in higher education and examines changes in human identity, consciousness, and the role of the divine in the age of artificial intelligence. It distinguishes between divine creation, which has intentionality, soul-bearing life and moral agency, and artificial creation, which is based on algorithms, data, and human design. It defies technocentric hope and theological hesitation, suggesting a way forward for theological reflection on human vocation, moral boundaries, and stewardship through Artificial Intelligence. In conclusion, this paper suggests that Artificial Intelligence can be viewed not as a replacement for God's creative power but as a catalyst for interdisciplinary dialogue and reflection within the academy, particularly concerning the relationship between innovation and theology, and their moral and ethical dimensions. It promotes an educationally sustainable approach that respects human dignity, spiritual understanding and moral duty while dealing with the challenges of ongoing technological change. Keywords: Artificial Intelligence, Ethical Innovation, Theology and Technology, Divine Creativity